Studies on the mechanism of ototoxic action of cisplatin and the antagonistic effect of polyphenolic compounds - Shengyu Han; Shengyu Han; Jinjun Sun; Jinjun Sun; Wenpeng Li; Wenpeng Li; Jihong Li; Haoming Yu; Haoming Yu; Shuai Wang; Yuhua Chi; Yuhua Chi (Frontiers in Pharmacology)
Cisplatin is a highly effective broad-spectrum anticancer drug, but its severe ototoxicity limits its clinical application. Cisplatin ototoxicity is mainly manifested as irreversible hearing loss, and its mechanism involves various pathways such as DNA damage, oxidative stress, inflammatory response, mitochondrial dysfunction, and ferroptosis. In recent years, natural polyphenols have shown great potential in combating cisplatin ototoxicity due to their powerful antioxidant, anti-inflammatory and anti-apoptotic properties.A variety of polyphenolic compounds, such as resveratrol, curcumin, quercetin, etc., can effectively attenuate the damage of cisplatin on Corti organs, spiral ganglion neurons and vascular striatum by scavenging free radicals, inhibiting the release of inflammatory factors, and regulating the expression of apoptosis-related proteins. In addition, some polyphenols can enhance the anti-tumour effect while antagonizing ototoxicity.Although polyphenols show good application prospects in the prevention and treatment of cisplatin ototoxicity, there are still some problems that need to be solved, such as the low bioavailability of polyphenols, the mechanism of action has not yet been fully elucidated, the optimal dosing regimen has not yet been determined, whether there is any superimposed effect of combining the various types of polyphenols, and whether the oral polyphenols can exert an otoprotective effect through the regulation of the intestinal flora through the intestinal-auricular axis.This study provides new insights into polyphenols as potential drug candidates for CIO by summarising the cytotoxic mechanisms of cisplatin and the mechanism of action of polyphenols targeting these mechanisms in order to retard the progression of CIO. It provides new ideas and approaches for the next step focusing on the development of highly effective and low-toxic polyphenols for clinical control of cisplatin ototoxicity.